Fractional Langevin equations involving ψ-Caputo type in a Banach space: a solution sets approach - ZENTAR, Oualid; ZIANE, Mohamed; Al HORANI, Mohammed (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
This paper investigates certain topological properties of the set of all global solutions for a class of nonlinear ψ-Caputo fractional Langevin equations. The nonlinearity, defined on an infinite-dimensional Banach space, is assumed to satisfy Nagumo-type growth conditions. An Aronszajn-type result is established using the nonlinear alternative for condensing operators, combined with the Browder–Gupta method. An illustrative example is provided to support the theoretical findings. Mathematics Subject Classification (2010): 34A08, 47H08, 34G20. Received 07 September 2025; Accepted 24 March 2026.